Skolehuset som kulturminne: Lokale verdier og nasjonal kulturminneforvaltning - Mydland, Leidulf (Tidsskrift for kulturforskning, 2011)
The one room schoolhouses in Norway reflect an era of reforms in education and development of democratic, social institutions in the late 19th century. Although the school reform was an achievement of great importance, the one room schoolhouses as objects of cultural heritage are not considered important by the heritage authorities, and not a single one is protected by law.  In spite of lack of national commitment, people in local communities have preserved these buildings both as local museums and for use as local meeting houses. The local approaches to these buildings as heritage differ from the Authorized Heritage Discourse (AHD) which does reflect a focus on architecture, age and relevance for the nation, safeguarded by professional antiquarians. The AHD in Norway is not in line with the National white papers and international charters and conventions, especially the Faro Convention which stresses the role of local participation, cooperation and need to involve everyone in society in the ongoing process of defining and managing cultural heritage. The challenge is how to ensure local participation when the AHD still reflects professionalism and predefined criteria for value assessment.